Default object view. Click to create a custom template, Node ID: 19310, Object ID: 29266

‘Proof’ that 2 = 1

‘Proof’ that 2 = 1

let a = b, then a2 = ab

a2 - b2 = ab-b2

(a-b)(a+b) = b(a-b)

a+b = b, substituting gives b+b = b

2b = b therefore 2 = 1

Where is the error made?

let a = b

then a2 = ab

a2 - b2 = ab-b2

(a-b)(a+b) = b(a-b)

a+b = b

substituting b+b = b

2b = b

2 = 1

Where is the error made?

You need to be aware that a – b = 0. This false proof relies on dividing both sides of an equation by zero which should not be done.

Yes

Yes